Plasmids, viruses and virus-like membrane vesicles from Thermococcales. (19th January 2011) - Soler, Nicolas; Gaudin, Marie; Marguet, Evelyne; Forterre, Patrick
Abstract : Several families of plasmids and viruses (PVs) have now been described in hyperthermophilic archaea of the order Thermococcales. One family of plasmids replicates by the rolling circle mechanism, whereas most other PVs probably replicate by the θ mode. PVs from Thermococcales encode novel families of DNA replication proteins that have only detectable homologues in other archaeal PVs. PVs from different families share a common gene pool and co-evolve with their hosts. Most Thermococcales also produce virus-like membrane vesicles similar to eukaryotic microparticles (ectosomes). Some membrane vesicles of Thermococcus nautilus harbour the plasmid pTN1, suggesting that vesicles can be involved in plasmid transfer between species.